The contrary conservation situations of two local critically endangered species, Vaccinium emarginatum (Ericaceae) and Elatostema platyphyllum (Urticaceae), growing on the eastern edge of the distribution - Shibabayashi, Mayu; Shimizu, Taiga; Tokuhiro, Chinatsu; Suyama, Yoshihisa; Sakaguchi, Shota; Ito, Takuro; Yu, Chih-Chieh; Chung, Kuo-Fang; Nagasawa, Jun’ichi; Shiuchi, Toshiaki; Kokubugata, Goro; Abe, Atsushi; et al. (Frontiers in Ecology and Evolution, 2023)
As biodiversity loss continues, there is an urgent need to develop efficient conservation measures to protect diversity with limited conservation resources. Conservation targets have generally been selected based on their population size, but more detailed assessments clarifying the phylogenetic genetic status, history, and phylogenetic uniqueness of rare species is crucial to set more appropriate and effective conservation measures. In Japan, the Act on Conservation of Endangered Species of Wild Fauna and Flora designated endangered plants with high conservation priority, but >40% of these species also grow overseas. We conducted comparative analyses based on ddRADseq and MIG-seq to evaluate the population conservation status and value of V. emarginatum and E. platyphyllum which are growing across national borders at the eastern edge of their species distribution range. The analyses revealed contrasting conservation status between the two species; the Japanese population of V. emarginatum had lower genetic diversity at the individual level and phylogenetically differentiated from Taiwanese populations, while that of E. platyphyllum had higher diversity at the individual level and is a relatively recent migrant with little phylogenetical differentiation from Taiwanese populations. The two species, which share the common feature of being critically rare in Japan, showed contrasting genetic/phylogenetic characteristics. This study provided useful information for appropriate conservation measures based on species’ phylogenetic traits and genetic diversity.